Rhizosphere microbiome selection by Epichloë endophytes of Festuca arundinacea - Roberts, Elizabeth Lewis; Ferraro, Aileen (Plant and Soil, 2015)
Aims: Loline alkaloids produced by Epichloë spp. are known to deter feeding by insect herbivores while also serving as a significant carbon source for certain epiphytic bacteria on tall fescue leaves. In this study we examined the role of loline alkaloids in attracting certain bacteria to the rhizosphere of tall fescue plants that harbor loline producing fungal endophytes. Methods: Population studies were used to compare the fitness of known loline catabolizing strains to other rhizosphere bacteria. Pyrosequencing of 16S rRNA fragments compared the composition of bacterial communities inhabiting the endophyte infected tall fescue (Festuca arundinacea) rhizosphere to those of endophyte free fescue plants. Results: Rhizosphere population studies demonstrated that loline catabolizing strains Burkholderia ambifaria 7R and Pseudomonas aureofaciens outcompete and suppress the growth of non-loline catabolizing strains. Pyrosequencing of 16S rRNA fragments showed greater percentages of certain plant growth promoting bacteria in rhizosperes seeded with B. ambifaria 7R than non-inoculated soils. Rhizospheres of endophyte infected plants showed higher species richness (Shannon diversity index = 4.03) over endophyte free rhizospheres (Shannon diversity index = 3.08) and a greater percentage of Firmicutes. Conclusions: The differences in microbial community composition between endophyte-infected and endophyte-free rhizospheres suggest that the presence of fungal endophytes influences microbial community structure. Loline alkaloid production may be one proxy by which the fungal endophyte shapes microbial communities, as evidenced by increased fitness of loline catabolizing bacteria in the tall fescue rhizosphere. © 2015, Springer International Publishing Switzerland.
Keywords: Bacteria (microorganisms); Burkholderia ambifaria; Endophyte; Epichloë spp; Festuca arundinacea; Firmicutes; Hexapoda; Loline alkaloids; Pseudomonas chlororaphis; Tall fescue; alkaloid; antifeedant; bacterium; community structure; dept.bio; diversity index; endophyte; fitness; fungus; grass; insect; microbial community; microorganism; rhizosphere; species richness

Designing a broad-spectrum integrative approach for cancer prevention and treatment. - Block, Keith I; Gyllenhaal, Charlotte; Lowe, Leroy; Amedei, Amedeo; Amin, A R M Ruhul; Amin, Amr; Aquilano, Katia; Arbiser, Jack; Arreola, Alexandra; Arzumanyan, Alla; Ashraf, S Salman; Azmi, Asfar S; et al. (Seminars in Cancer Biology, 2015)
Targeted therapies and the consequent adoption of "personalized" oncology have achieved notable successes in some cancers; however, significant problems remain with this approach. Many targeted therapies are highly toxic, costs are extremely high, and most patients experience relapse after a few disease-free months. Relapses arise from genetic heterogeneity in tumors, which harbor therapy-resistant immortalized cells that have adopted alternate and compensatory pathways (i.e., pathways that are not reliant upon the same mechanisms as those which have been targeted). To address these limitations, an international task force of 180 scientists was assembled to explore the concept of a low-toxicity "broad-spectrum" therapeutic approach that could simultaneously target many key pathways and mechanisms. Using cancer hallmark phenotypes and the tumor microenvironment to account for the various aspects of relevant cancer biology, interdisciplinary teams reviewed each hallmark area and nominated a wide range of high-priority targets (74 in total) that could be modified to improve patient outcomes. For these targets, corresponding low-toxicity therapeutic approaches were then suggested, many of which were phytochemicals. Proposed actions on each target and all of the approaches were further reviewed for known effects on other hallmark areas and the tumor microenvironment. Potential contrary or procarcinogenic effects were found for 3.9% of the relationships between targets and hallmarks, and mixed evidence of complementary and contrary relationships was found for 7.1%. Approximately 67% of the relationships revealed potentially complementary effects, and the remainder had no known relationship. Among the approaches, 1.1% had contrary, 2.8% had mixed and 62.1% had complementary relationships. These results suggest that a broad-spectrum approach should be feasible from a safety standpoint. This novel approach has potential to be relatively inexpensive, it should help us address stages and types of cancer that lack conventional treatment, and it may reduce relapse risks. A proposed agenda for future research is offered. Copyright © 2015 The Authors. Published by Elsevier Ltd.. All rights reserved.
Keywords: *Genetic Heterogeneity; *Molecular Targeted Therapy; *Neoplasms/th [Therapy]; *Precision Medicine; Antineoplastic Agents, Phytogenic; Antineoplastic Agents, Phytogenic/tu [Therapeutic Use]; Cancer hallmarks; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/ge [Genetics]; Genetic Heterogeneity; Humans; Integrative medicine; Molecular Targeted Therapy; Multi-targeted; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pa [Pathology]; Neoplasms/pc [Prevention & Control]; Phytochemicals; Precision Medicine; Review; Signal Transduction; Targeted therapy; Tumor Microenvironment; Tumor Microenvironment/ge [Genetics]; anthocyanin; antineoplastic activity; antineoplastic agent; apoptosis; belinostat; berberine; breast cancer; cancer prevention; cancer therapy; cell immortalization; colorectal cancer; curcumin; deguelin; dept.bio; dietary intake; dinaciclib; drug cost; drug efficacy; drug resistance; drug safety; drug targeting; enterolactone; epigallocatechin gallate; gamma linolenic acid; genetic heterogeneity; genetics; genistein; genomic instability; gossypol; human; icosapentaenoic acid; imetelstat; inflammation; integrative medicine; interdisciplinary communication; kaempferol; luteolin; lycopene; melatonin; metastasis; metastasis inhibition; molecularly targeted therapy; naringenin; natural product; nonhuman; palbociclib; patent; pathology; perillyl alcohol; personalized medicine; phenotype; phytochemistry; recurrence risk; resveratrol; risk reduction; romidepsin; selinexor; signal transduction; silibinin; soybean; triptolide; tumor escape; tumor invasion; tumor microenvironment; tumor vascularization; unindexed drug; vorinostat; withaferin A; zerumbone

Cancer prevention and therapy through the modulation of the tumor microenvironment. - Casey, Stephanie C; Amedei, Amedeo; Aquilano, Katia; Azmi, Asfar S; Benencia, Fabian; Bhakta, Dipita; Bilsland, Alan E; Boosani, Chandra S; Chen, Sophie; Ciriolo, Maria Rosa; Crawford, Sarah; Fujii, Hiromasa; et al. (Seminars in Cancer Biology, 2015)
Cancer arises in the context of an in vivo tumor microenvironment. This microenvironment is both a cause and consequence of tumorigenesis. Tumor and host cells co-evolve dynamically through indirect and direct cellular interactions, eliciting multiscale effects on many biological programs, including cellular proliferation, growth, and metabolism, as well as angiogenesis and hypoxia and innate and adaptive immunity. Here we highlight specific biological processes that could be exploited as targets for the prevention and therapy of cancer. Specifically, we describe how inhibition of targets such as cholesterol synthesis and metabolites, reactive oxygen species and hypoxia, macrophage activation and conversion, indoleamine 2,3-dioxygenase regulation of dendritic cells, vascular endothelial growth factor regulation of angiogenesis, fibrosis inhibition, endoglin, and Janus kinase signaling emerge as examples of important potential nexuses in the regulation of tumorigenesis and the tumor microenvironment that can be targeted. We have also identified therapeutic agents as approaches, in particular natural products such as berberine, resveratrol, onionin A, epigallocatechin gallate, genistein, curcumin, naringenin, desoxyrhapontigenin, piperine, and zerumbone, that may warrant further investigation to target the tumor microenvironment for the treatment and/or prevention of cancer. Copyright © 2015 Elsevier Ltd. All rights reserved.
Keywords: *Carcinogenesis/de [Drug Effects]; *Neoplasms/dt [Drug Therapy]; *Neovascularization, Pathologic/dt [Drug Therapy]; *Tumor Microenvironment/ge [Genetics]; 5 chloro n2 [1 (5 fluoro 2 pyrimidinyl)ethyl] n4 (5 methyl 1h pyrazol 3 yl) 2,4 pyrimidinediamine; Antineoplastic Agents; Antineoplastic Agents/tu [Therapeutic Use]; Cancer biology; Cancer prevention; Cancer therapy; Carcinogenesis; Carcinogenesis/ge [Genetics]; Cell Proliferation; Cell Proliferation/de [Drug Effects]; Humans; Janus kinase; Molecular Targeted Therapy; Neoplasms; Neoplasms/ge [Genetics]; Neoplasms/pc [Prevention & Control]; Neovascularization, Pathologic; Neovascularization, Pathologic/ge [Genetics]; Neovascularization, Pathologic/pc [Prevention & Control]; Review; Signal Transduction; Tumor Microenvironment; Tumor Microenvironment/de [Drug Effects]; Tumor microenvironment; antiinflammatory activity; antineoplastic agent; antioxidant activity; antiproliferative activity; apoptosis; bacterial infection; berberine; bevacizumab; cancer prevention; cancer therapy; candidiasis; carcinogenesis; cell proliferation; cholesterol synthesis; cisplatin; colorectal cancer; curcumin; cytokine production; dendritic cell; dept.bio; desoxyrhapontigenin; drug cytotoxicity; drug effects; drug potentiation; drug structure; drug targeting; endoglin; epigallocatechin gallate; fatty liver; fibrosis; genetics; genistein; genomic instability; glioblastoma; human; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypercholesterolemia; hyperlipidemia; hypoxia; indoleamine 2,3 dioxygenase; interleukin 6; kidney cancer; liver cancer; liver cell carcinoma; lung cancer; lung metastasis; macrophage activation; metastasis inhibition; molecularly targeted therapy; mycosis; naringenin; natural product; non insulin dependent diabetes mellitus; nonhuman; obesity; oncogene; onionin A; paclitaxel; pancreas tumor; parasitosis; piperine; reactive oxygen metabolite; resveratrol; signal transduction; sorafenib; stomach cancer; sunitinib; tamoxifen; tumor associated leukocyte; tumor escape; tumor invasion; tumor microenvironment

On the origins of autism: The Quantitative Threshold Exposure hypothesis. - Crawford, S (Medical hypotheses, 2015)
The Quantitative Threshold Exposure (QTE) hypothesis is a multifactorial threshold model that accounts for the cumulative effects of risk factor exposure in both the causation of autism spectrum disorder (ASD) and its dramatic increase over the past 30 years. The QTE hypothesis proposes that ASD is triggered by the cumulative effects of high-level exposure to endogenous and environmental factors that act as antigens to impair normal immune system (IS) and associated central nervous system (CNS) functions during critical developmental stages. The quantitative threshold parameters that comprise a cumulative risk for the development of ASD are identified by the assessment of documented epidemiological factors that, in sum, determine the likelihood that ASD will occur as a result of their effects on critically integrated IS and CNS pathways active during prenatal, neo-natal and early childhood brain maturation. The model proposes an explanation for the relationship between critical developmental stages of brain/immune system development in conjunction with the quantitative effects of genetic and environmental risk factors that may interface with these critical developmental windows. This model may be useful even when the individual contributions of specific risk factors cannot be quantified, as it proposes that the combined quantitative level of exposure to risk factors for ASD rather than exposure to any one risk factor per se defines threshold occurrence rates. Copyright © 2015 Elsevier Ltd. All rights reserved.
Keywords: *Autistic Disorder/ep [Epidemiology]; *Environmental Exposure/sn [Statistics & Numerical Data]; *Epidemiologic Methods; *Risk Assessment/mt [Methods]; *Threshold Limit Values; 5 HTT gene; 5 hydroxytryptophan; Article; Autistic Disorder; Causality; DNA polymorphism; Environmental Exposure; Epidemiologic Methods; Evidence-Based Medicine; Humans; Incidence; RLN gene; Risk Assessment; Threshold Limit Values; autism; autoimmune disease; brain dysfunction; brain maturation; cannabinoid 1 receptor; cannabinoid 2 receptor; cannabis use; central nervous system function; childhood disease; childhood feeding; copy number variation; dept.bio; developmental stage; disease association; disease severity; environmental exposure; environmental factor; epidemiological data; evidence based medicine; feeding; feeding behavior; genetic association; genetic predisposition; genetic risk; high risk population; human; hypothesis; immunoreactivity; incidence; infant feeding; intrauterine infection; n acetylgalactosaminidase; nervous system development; nonbiological model; nonhuman; pediatric infectious disease; perinatal period; prevalence; procedures; quantitative threshold exposure hypothesis; reelin; risk assessment; risk factor; statistics and numerical data; tetrahydrocannabinol; threshold limit value; threshold model; unclassified drug; unclassified enzyme; vitamin D deficiency

Physiological responses related to increased grain yield under drought in the first biotechnology‐derived drought‐tolerant maize - Nemali, Krishna S; Bonin, Christopher P; Dohleman, Frank G; Stephens, Mike; Reeves, William; Nelson, Donald E; Castiglioni, Paolo; Whitsel, Joy; Sammons, Bernard; Silady, Rebecca A; Anstrom, Donald; Sharp, Robert E; et al. (Plant Cell and Environment, 2015)
Maize (Zea mays ssp. mays L.) is highly susceptible to drought stress. This work focused on whole-plant physiological mechanisms by which a biotechnology-derived maize event expressing bacterial cold shock protein B (CspB), MON 87460, increased grain yield under drought. Plants of MON 87460 and a conventional control (hereafter 'control') were tested in the field under well-watered (WW) and water-limited (WL) treatments imposed during mid-vegetative to mid-reproductive stages during 2009-2011. Across years, average grain yield increased by 6% in MON 87460 compared with control under WL conditions. This was associated with higher soil water content at 0.5 m depth during the treatment phase, increased ear growth, decreased leaf area, leaf dry weight and sap flow rate during silking, increased kernel number and harvest index in MON 87460 than the control. No consistent differences were observed under WW conditions. This indicates that MON 87460 acclimated better under WL conditions than the control by lowering leaf growth which decreased water use during silking, thereby eliciting lower stress under WL conditions. These physiological responses in MON 87460 under WL conditions resulted in increased ear growth during silking, which subsequently increased the kernel number, harvest index and grain yield compared to the control. Copyright © 2014 The Authors. Plant, Cell & Environment published by John Wiley & Sons Ltd.
Keywords: *Biotechnology/mt [Methods]; *Droughts; *Zea mays/ph [Physiology]; Bacteria (microorganisms); Bacterial Proteins; Bacterial Proteins/ge [Genetics]; Biotechnology; CspB; Droughts; Ear; Edible Grain; Harvest index; Leaf area; Plant Leaves; Plant Leaves/ph [Physiology]; Plants, Genetically Modified; Plants, Genetically Modified/ph [Physiology]; Sap flow; Soil; Soil water content; Soil/ch [Chemistry]; Water use; Yield; Zea mays; acclimation; adaptation; bacterial protein; biotechnology; chemistry; cold-shock protein CspB, Bacteria; crop yield; dept.bio; drought; drought stress; food grain; genetics; index method; leaf area; maize; physiological response; physiology; plant leaf; procedures; protein; sap flow; soil; soil water; tolerance; transgenic plant; water use efficiency